Chronic heart failure and hypoalbuminemia are risk factors of poorer mRNA SARS-CoV-2 vaccine response in maintenance Hemodialysis patients (the COVaccinDia study) - Pierre Laurent; Marianne Renou; Najeh El Esper; Gabriel Choukroun; Pierre Pommerolle; Sébastien Laburthe; Pauline Caillard (BMC Nephrology, 2025)
Abstract Background Chronic kidney disease represents an immunocompromising condition and a cause of a lower vaccine efficacy, even in patients undergoing maintenance dialysis. Recent SARS-CoV-2 outbreaks have prompted clinicians to better understand the underlying mechanisms and establish more suitable vaccination schedules. Methods In a single-center, retrospective, observational study of patients undergoing maintenance dialysis in France, we studied the factors associated with the intensity of the humoral response to a SARS-CoV-2 vaccine in this population, including specific dialysis-related variables. Results After having received three doses of SARS-CoV-2 mRNA vaccine, a cohort of 80 patients was divided into low-responders (28 patients with an anti-SARS-CoV-2 antibody level of 50-1830 AU/mL) and responders (52 patients with an antibody level > 1830 AU/mL). We found that chronic heart failure (p < 0.00001), higher performance status (p = 0.004), hypoalbuminemia (p < 0.001), lymphopenia (p = 0.003), Rhesus status positivity (p = 0.02), and absence of response to a hepatitis B virus vaccine (p = 0.02) were associated with a poor response to a third dose of SARS-CoV-2 vaccine. In contrast, none of the dialysis-related variables were associated with the vaccine response. In multivariate logistic regression, chronic heart failure (p < 0.0001) and hypoalbuminemia (p = 0.0004) remained associated with a lower humoral response to SARS-CoV-2 vaccine. Conclusions Our results showed that chronic heart failure and hypoalbuminemia were factors associated with a poor humoral response after three doses of SARS-CoV-2 vaccine. However, we found no association between specific dialysis-related variables and the anti-SARS-CoV-2 antibody titer.